A PILOT STUDY ON NAAD PARIKSHA (PERCUSSION) IN PATIENTS WITH LIVER CIRRHOSIS - Dr. Chintamani Arun Kodolikar; Vd. Arun Vaidya; Dr. Hemant Toshikhane (The Bioscan, 2025)
BACKGROUND: Naad Pariksha (Classical Percussion), a traditional diagnostic tool in Ayurveda, involves the assessment of internal organ states through sound analysis during percussion. Liver cirrhosis, a chronic degenerative condition marked by fibrosis and altered hepatic architecture, significantly affects abdominal resonance. OBJECTIVE: This pilot study aims to explore the clinical utility of Naad Pariksha in patients diagnosed with liver cirrhosis and to identify dominant Naad patterns. METHODS: A total of 50 patients with liver cirrhosis (diagnosed on the basis of clinical and radiologic findings) were assessed using Panchabhautik Naad Pariksha (traditionally developed abdominal percussion methods of Vaidya Atmaram Vaman Shastri Datar). Percussion was performed on standard abdominal zones (nine quadrants of abdomen), and the quality of sound was categorized based on Panchamahabhuta (type of sounds manually assessed on the basis of frequency, intensity and peach-purely subjective method) dominance: Parthiv (earthy) Naad, Apya (watery) Naad, Tejas (fiery) Naad, Vayaviya (airy) Naad, and Akashiya (ethereal) Naad. Results: In the majority of patients, Naad with predominant Parthiv characteristics was observed. These sounds were described as heavy, dull, and resistant, typically found over ascetic regions and fibrotic liver zones. Conclusion: The findings suggest that Parthiv Naad [42 patients (84%)] is dominant in cirrhotic livers, possibly due to fibrosis and fluid retention, correlating with the earthy and solid nature of Parthiva Mahabhuta. Naad Pariksha may serve as a valuable adjunct in the Ayurvedic assessment of liver pathologies. KEYWORDS Naad Pariksha, Panchabhautika Naad, Liver Cirrhosis, Ayurvedic Diagnosis, Abdominal Percussion